Seismic resilience design of prefabricated modular pressurized buildings - Zhiwu Ye; Haifeng Bu; Zhimao Liu; Deng Lu; Dong Min; Hongbo Shan (Resilient Cities and Structures, 2025)
The seismic intensity is generally high in the Qinghai-Tibet Plateau region of China. The seismic performance of the new prefabricated modular pressurized buildings used to solve the plateau response is insufficient. To solve this problem, the small friction pendulum bearing (FPB) isolation design is proposed for modular pressurized buildings. Firstly, a simplified model of cross-truss support for the pressurized module is proposed to simplify the modeling and calculation of the pressurized buildings. The reasonability of the simplified model is verified by comparing the refined finite element model. Subsequently, according to the FPB design process for modular pressurized buildings, a small FPB for isolation is provided for a two-story modular pressurized building under 8-degree fortification earthquakes. Lastly, the seismic effectiveness and constructional feasibility of the isolation structure are verified compared with the non-isolated structure using dynamic time-history analysis. The study results show that the size of FPBs for modular pressurized buildings should consider both displacement and dimension requirements to weigh seismic isolation performance and installation feasibility, respectively. When adopting FPBs, the response of the structure is significantly reduced, and the seismic isolation effect is obvious. The proposed construction process can improve the seismic resilience of the prefabricated modular pressurized buildings by replacing post-earthquake damaged components quickly. It provides ideas for the seismic isolation design of the prefabricated modular pressurized buildings in high seismic intensity areas.